Pengembangan Transferable Skills dalam Pembelajaran Produktif Sekolah Menengah Kejuruan di Era Industri 4.0 - Yulianto Eko Wibowo; Rodia Syamwil (Department of Mechanical Engineering Education, 2019)
The demand for industries in the fulfilment of labour is more complex because it must be suitable for the competencies in hard skills and soft skills. Vocational High School (SMK) becomes pivotal in fulfilling the needs of industrial labour. The transferable skills to be developed are communication, cooperation, discipline and responsibility. The purpose of this study is to analyze those transferable skills in the learning process of a productive course at vocational high school and how much have the students absorb those soft skills. This research is descriptive research using a mixed-method approach. The results show the soft skills in productive-course learning in numbers: communication ability 87.18 % (very good criteria), cooperation 86.14 % (very good criteria), discipline 89.64 % (very good criteria), and responsibility 86.78 % (very good criteria). Whereas for the absorption of the soft skills: communication 83.37 % (good criteria), cooperation 86.16 % (very good criteria), discipline 80.43 % (good criteria) and responsibility 82.07 % (good criteria). The implementation of transferable skills in productive-course learning in SMK has succeeded and is following the objectives and demands of the Industrial Revolution 4.0. This can be reinforced by accustomization of character and behaviour of the students so that they always communicate actively, be cooperative, have discipline and show responsibility in the learning process.Tuntutan industri dalam pemenuhan tenaga kerja era Industri 4.0 bernilai lebih kompleks karena harus disesuaikan dengan kompetensi hard skills maupun soft skills. SMK menjadi point penting dalam pemenuhan kebutuhan tenaga kerja industri. Transferable skills yang dikembangkan adalah komunikasi, kerjasama, dan kedisiplinan dan tanggung jawab. Tujuannya adalah untuk menganalisis pengembangan transferable skills dalam pembelajaran produktif di SMK dan keterserapan soft skills siswa SMK. Penelitian ini merupakan penelitian deskriptif pendekatan mix methods. Transferable skills dalam pembelajaran produktif SMK menghasilkan pengembangan soft skill kemampuan berkomunikasi mencapai 87.18% kriteria sangat baik, soft skill kerjasama mencapai 86.14% kriteria sangat baik, soft skill disiplin 89.64% kriteria sangat baik dan soft skill tanggung jawab 86.78% kriteria sangat baik. Keterserapan soft skill kemampuan berkomunikasi mencapai 83.37% kriteria baik, soft skill kerjasama mencapai 86.16% kriteria sangat baik, soft skill disiplin mencapai 80.43% kriteria baik, dan soft skill tanggung jawab 82.07 kriteria baik. Transferable skills dalam pembelajaran produktif SMK di Kota Semarang sudah dilaksanakan dengan baik sesuai tujuan dan tuntutan era Industri 4.0. Hal ini perlu dikuatkan dengan pembiasaan sifat dan sikap siswa untuk selalu aktif berkomunikasi, bekerjasama, disiplin dan bertanggung jawab dalam proses pembelajaran.